Biological Correlates of Extinction Risk in Resident Philippine Avifauna - Kittelberger, Kyle D.; Neate-Clegg, Montague H. C.; Blount, J. David; Posa, Mary Rose C.; McLaughlin, John; Şekercioğlu, Çağan Hakkı (Frontiers in Ecology and Evolution, 2021)
The majority of the world’s biodiversity occurs in the tropics, but human actions in these regions have precipitated an extinction crisis due to habitat degradation, overexploitation, and climate change. Understanding which ecological, biogeographical, and life-history traits predict extinction risk is critical for conserving species. The Philippines is a hotspot of biodiversity and endemism, but it is a region that also suffers from an extremely high level of deforestation, habitat degradation, and wildlife exploitation. We investigated the biological correlates of extinction risk based on the IUCN Red List threat status among resident Philippine birds using a broad range of ecological, biogeographical, and life history traits previously identified as correlates of extinction risk in birds. We found strong support across competing models for endemism, narrower elevational ranges, high forest dependency, and larger body size as correlates significantly associated with extinction risk. Additionally, we compared observed threat status with threat status fitted by our model, finding fourteen species that are not currently recognized by the IUCN Red List as threatened that may be more threatened than currently believed and therefore warrant heightened conservation focus, and predicted threat statuses for the four Philippine Data Deficient bird species. We also assessed species described in recent taxonomic splits that are recognized by BirdLife International, finding twelve species that have a fitted threat status more severe than their IUCN-designated ones. Our findings provide a framework for avian conservation efforts to identify birds with specific biological correlates that increase a species’ vulnerability to extinction both in the Philippine Archipelago and elsewhere on other tropical islands.